1997
DOI: 10.1017/s0954579497001454
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Variant of Ecological Systems Theory (PVEST): A self-organization perspective in context

Abstract: A framework that emphasizes and integrates individuals' intersubjective experiences with Bronfenbrenner's ecological systems theory (PVEST) is introduced and compared with self-organizational perspectives. Similarities, differences and advantages of each framework are described. In a demonstration of PVEST's utility, a subset of data from the 3rd year of a longitudinal study (14-to 16-year-old middle adolescent African-Americans) is used for examining an achievement variable: negative learning attitude. Explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
647
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 543 publications
(679 citation statements)
references
References 9 publications
30
647
1
1
Order By: Relevance
“…Several extant theoretical frameworks have highlighted the central role of racerelated experiences in shaping developmental trajectories among ethnic minority youth (e.g., Garcia-Coll et al, 1996;Ogbu, 1978Ogbu, , 1981Spencer et al, 1997). The current investigation draws on Garcia-Coll and colleagues ' integrative model (1996) for the study of ethnic minority child development, which emphasizes the importance of race and race-related experiences in the development of minority children.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Several extant theoretical frameworks have highlighted the central role of racerelated experiences in shaping developmental trajectories among ethnic minority youth (e.g., Garcia-Coll et al, 1996;Ogbu, 1978Ogbu, , 1981Spencer et al, 1997). The current investigation draws on Garcia-Coll and colleagues ' integrative model (1996) for the study of ethnic minority child development, which emphasizes the importance of race and race-related experiences in the development of minority children.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…American youth (Graham & Juvonen, 2002;Spencer et al, 1997), as well as that specifically due to race (DuBois et al, 2002;Fisher et al, 2000;.…”
Section: Racial Climate and Achievement Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The PVEST was derived from Bonfenbrenner's Ecological Systems Theory and expounded upon by Spencer et al (1997). According to the APA taskforce on resilience, "Resilience in African American Children and Adolescents: A Vision for Optimal Development" (APA, Task Force on Resilience and Strength in Black Children and Adolescents, 2008), the PVEST theory serves as one of the most integrative approaches for assessing academic resilience and identity formation for young African American adults.…”
mentioning
confidence: 99%
“…[12,46,47] For example, in a study investigating urban fifth graders as they made connections between their science classroom and their lived experiences, a fifth grade girl commented that she visited a friend as she gardened and when her friend dug into the ground she saw different colors of soil and remembered a concept she learned from her science teacher. [48] Nasir [14] found that boys did demonstrate more sophisticated understanding of statistics as they matriculated from middle school to high school basketball teams.…”
Section: Mathematical and Science Knowledgementioning
confidence: 99%